Differences in the seasonal development of perithecia by Neonectria ditissima on apple trees across Northern Europe - Børve, Jorunn; Pampus, Katharina; Haikonen, Tuuli; Podavkova, Andrea; Myren, Gaute; Weber, Roland W. S. (Springer Nature, 2024)
Ascospores discharged at rainfall and dispersed by wind can provide long-distance spread of the European canker fungus, Neonectria ditissima. Ascospores are produced by perithecia which are the sexual reproductive stage. Diffuse knowledge exists on the seasonal pattern of perithecium formation under different climatic conditions. Therefore, the development of perithecia was observed for several successive seasons at five sites in three Northern European countries. In Norway and Finland, ripe perithecia were commonly recorded throughout the year, and on individual cankers continuously for up to 28 months. In contrast, asexual reproductive structures (sporodochia) were confined to the growing season in both countries. In Northern Germany an average of 51% of cankers developed ripe perithecia by late winter, and perithecial senescence ensued in late spring. On average, ripe perithecia were present on cankers for 22 weeks. In contrast, sporodochia were observed all year round. The timing of perithecium maturation correlated with the number of days with > 2 mm rainfall in July–September. The presence of mature perithecia and sporodochia for different lengths of time in different countries has implications for regional disease management strategies.
Keywords: hedelmäpuut; epidemiologia; itiöt; kotelosienet; Neonectria ditissima